RADIOLOGICAL ASSESSMENT OF SOME NATURAL SOURCES OF IONIZING RADIATION IN THE NOVGOROD REGION - A. P. Rosolovskij (Радиационная гигиена)
This article presents the assessment of some natural sources of ionizing radiation in theNovgorodregion. Among natural environment factors affecting human health in the region from radiological standpoint radon and it’s progeny are most hazardous. This is due to a very high contamination by uranium (radium) of some geological formations located at the depth from several meters to several dozen meters from the earth level. Massive exploration of uranium in the region conducted on more than 30-40 blocs identified the two potentially radon-hazardous areas totaling about 25500 square kilometers: Starorusskaya and BorovitchskoLiubytinskaya. These territories contain most of the identified radioactive anomalies in the rocks, underground and ground waters. Such anomalies are typically observed at depths not exceeding 100 m.On the basis of the anomalies’, the study zoning of theNovgorodregion was conducted in accordance with the severity of potential radon hazard. Local radon-hazardous spots were pinpointed as well as their impact upon the population health. The enrichment of the rocks creates the premises for radon emission into soil air, then into the atmosphere and into dwellings. People continuously living in a house with high radon content in the air are subject to the risk of lung or upper respiratory airway cancer.The objective is to substantiate the urgency of prolongation of Radon Program.Radon, the main radiological hazard for theNovgorodregion. The study of its’ effect upon local potentially hazardous spots. Territorial radon hazard-specific zoning, determination of causality in relation to the lungand upper respiratory airway cancer.